2004
DOI: 10.1002/mrd.20107
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that P36, a human sperm acrosomal antigen involved in the fertilization process is triosephosphate isomerase

Abstract: P36 is one of the immunodominant sperm antigens identified by antibodies eluted from the spermatozoa of infertile men. In a previous study, we isolated and characterized this auto-antigen as a glycoprotein with several isoforms. Specific rabbit antibodies were produced to investigate sperm topography and the role of P36 in the fertilization process and we showed that P36 is present on the equatorial segment of acrosome-reacted spermatozoa and is involved in sperm-binding and the penetration of zona-free hamste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…A testis-specific mRNA for TPI1 has been isolated from the rat testis [68]. Immunofluorescence experiments demonstrated that TPI is localized in the human sperm head [69]; however, further analysis should be performed to confirm the proper localization of the TPI protein using permeabilized sperm. In this report, we demonstrate the presence of three isoforms of TPI1 protein in epididymal mouse sperm.…”
Section: Discussionmentioning
confidence: 99%
“…A testis-specific mRNA for TPI1 has been isolated from the rat testis [68]. Immunofluorescence experiments demonstrated that TPI is localized in the human sperm head [69]; however, further analysis should be performed to confirm the proper localization of the TPI protein using permeabilized sperm. In this report, we demonstrate the presence of three isoforms of TPI1 protein in epididymal mouse sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Other germ cell-specific glycolytic isozymes have been described that differ either in sequence, activity, or other characteristics for aldolase (Gillis and Tamblyn, 1984), triose-phosphate isomerase (Auer et al, 2004), glyceraldehyde 3-phosphate dehydrogenase (GAPD-S) (Welch et al, 1992), phosphoglycerate kinase (Boer et al, 1987), enolase (Edwards and Grootegoed, 1983), and pyruvate kinase (Feiden et al, 2007), as well as for the extra-glycolytic but related enzyme lactate dehydrogenase (LDH-C4) (Zhong and Kleene, 1999) (Zinkham, 1968). …”
Section: Discussionmentioning
confidence: 99%
“…Mouse IgG was purchased from Sigma. The pAb against P36/TPI, which stains the acrosomal membrane, was a gift from J. Auer [14]. Rabbit polyclonal antibodies against RAB6 (a Golgi vesicle marker) and against RAB5 (an endocytic vesicle marker) were obtained from Santa Cruz Biotechnology.…”
Section: Specific Antibodiesmentioning
confidence: 99%